2013
DOI: 10.1111/jvp.12043
|View full text |Cite
|
Sign up to set email alerts
|

Depletion study and estimation of the withdrawal period for enrofloxacin in pacu (Piaractus mesopotamicus)

Abstract: Defining the pharmacokinetic parameters and depletion intervals for antimicrobials used in fish will help in the development of important guidelines for future regulations by Brazilian agencies on the use of these substances in fish farming. This paper presents a depletion study for enrofloxacin (ENR) and its main metabolite, ciprofloxacin (CIP), in pacu (Piaractus mesopotamicus) fillets. The depletion study was carried out under monitored environmental conditions, with the temperature controlled at 27 °C to m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
6
1
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(9 citation statements)
references
References 33 publications
0
6
1
2
Order By: Relevance
“…For the WDT of ENR, our findings in pigs were 5 days, which was similar to 5 or 6 days in poultry in previous reports (San Martin et al, 2010; Terrado-Campos et al, 2017). The previous studies revealed that after exposure to ENR at a dose of 10 mg/kg, the WDT was 5, 7, and 10 days in pigs (Delsol et al, 2004; San et al, 2007; Liu et al, 2011), and 23 days in piaractus mesopotamicus (Luo et al, 2010), most of which was far longer than that in our study (Wiuff et al, 2002; San et al, 2007; Godoy et al, 2011; Paschoal et al, 2013). Therefore, EEG had an advantage with a short WDT.…”
Section: Discussioncontrasting
confidence: 42%
See 1 more Smart Citation
“…For the WDT of ENR, our findings in pigs were 5 days, which was similar to 5 or 6 days in poultry in previous reports (San Martin et al, 2010; Terrado-Campos et al, 2017). The previous studies revealed that after exposure to ENR at a dose of 10 mg/kg, the WDT was 5, 7, and 10 days in pigs (Delsol et al, 2004; San et al, 2007; Liu et al, 2011), and 23 days in piaractus mesopotamicus (Luo et al, 2010), most of which was far longer than that in our study (Wiuff et al, 2002; San et al, 2007; Godoy et al, 2011; Paschoal et al, 2013). Therefore, EEG had an advantage with a short WDT.…”
Section: Discussioncontrasting
confidence: 42%
“…Previous reports had established a close link between the respiratory disease risk and the productivity decrease in animals (Godoy et al, 2011; Paschoal et al, 2013; Hassanpouraghdam et al, 2015; Sala et al, 2015). Generally, the strain with MIC 95 or MIC 90 was the preference for establishment of infection model and indicators for clinical treatment.…”
Section: Discussionmentioning
confidence: 89%
“…The plasma pharmacokinetics of enrofloxacin has been reported in some fish species, such as crucian carp (11,12), large yellow croaker (13), tilapia (14), snakehead fish (15), brown turbot (16), and salmonids (17). In addition to those pharmacokinetics studies, the tissue distribution of enrofloxacin has also been reported in aquaculture species, including northern snakeheads (18), rainbow trout (19,20), grass carp (21), largemouth bass (22), and pacu (23). Those previous results indicated that the plasma and tissues kinetics of enrofloxacin might be strongly influenced by fish species, body conditions, routes of administration, water temperature, and other environmental factors.…”
Section: Introductionmentioning
confidence: 96%
“…Freshwater colossomid fish, particularly pacu ( P. mesopotamicus ), are widely farmed in many South American countries, with estimated annual production reaching 150,000 tons in Brazil alone (Fontes, Nikolik, Rasmussen & Ikeda, ). Pacu has a high carcass lipid content, which is a factor that can directly affect drug metabolism by the species (Paschoal, Quesada, Gonçalves, Cyrino & Reyes, ).…”
Section: Introductionmentioning
confidence: 99%